Effect of counselling on the family function of intimate partner violence victims attending antenatal clinic in a tertiary hospital in North Central Nigeria - B. O. Akor; L. A. Moses; N. D. Baamlong; L. L. Shedul; A. S. Haruna; J. M. Abu; O. U. Chira; N. R. Ripiye; R. A. Abdulkareem (South African Family Practice)
Background and aim: Intimate partner violence (IPV) is a global problem. Family dysfunction is an integral characteristic of IPV homes. However, not much has been done regarding restoration of these families. The aim of this study was to explore the effect of counselling on the family function of pregnant IPV victims, with a view to recommending an appropriate interventional strategy. Methods: The study was a single-blinded randomised controlled trial of pregnant IPV victims. The Abuse Assessment Scale (AAS) was used to recruit 72 IPV victims who were randomised into the control and intervention arms of 36 each. Their sociodemographic data were collected. The family function of the victims was assessed using the SCORE-15 index of family function at the beginning the study. The intervention arm had three sessions of counselling lasting one to two hours fortnightly using the SOS DoC protocol. The family function was repeated post intervention. Data were analysed using SPSS version 20 and a p-value of 0.05 was considered significant. Results: The majority (82%) of the IPV victims had dysfunctional families. Baseline mean family function score across the groups showed no statistically significant difference. Post intervention, the mean family function score improved from 2.92 ± 0.92 to 2.16 ± 0.63 and this change was statistically significant (p 0.0001). In the control arm, the change from 2.48 ± 0.73 to 2.29 ± 0.82 was not statistically significant (p = 0.116). Conclusion: Short-term counselling significantly improved the family function of IPV victims.